Tympanosclerosis revisited - Kaur, Kamaljit (Springer India, 2006)
Tympanosclerosis is a common clinico-pathological entity encountered by the otosurgeon. Its pathogenesis and optimum management have eluded the otologists since time immemorial. The present study was undertaken to study the incidence of tympanosclerosis amongst patients with chronic suppurative otitis media and to study the correlation between the degree of hearing loss and the site of tympanosclerosis. Audiometric and operative findings of 200 patients of chronic suppurative otitis media were analysed. The incidence of tympanosclerosis was found to be 19% (3d cases out of 200 patients). Most cases of tympanosclerosis had a dry ear on presentation (78.9%). When tympanosclerosis was confined only to the tympanic membrane. 83.3% of the cases had an air-bone-gap less than 40 dB. On the other hand, when tympanosclerosis affected both the tympanic membrane and the middle ear. 75% of the cases had an air-bone-gap more than 40 dB. The hearing loss associated with tympanosclerosis was of the conductive type in the majority of cases. Ossicular mobility was found to be normal in 71.1% of the cases.